Hukum ar-Radha’ah dalam Islam: Teks Al-Qur'an, Hadits, dan Ijtihad Sahabat - Muji, Muji; Ilhamsyah, Rizal (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2024)
This study explores the law of ar-Radha’ah (breastfeeding) in Islam, examining it through the lens of the Qur'an, hadith, and the ijtihad of the Companions. Breastfeeding has implications beyond biological needs, affecting legal relationships like mahram and marriage restrictions. While ar-Radha’ah is addressed in the Qur'an and hadith, evolving societal and legal contexts call for further understanding and application. This study, therefore, examines the Companions' use of ijtihad to clarify these laws in response to issues of their time. The study aims to analyze the legal foundations of ar-Radha’ah in the Qur'an and hadith, emphasizing the role of the Companions' ijtihad in its development. Using descriptive qualitative analysis and a literature review, it includes Qur'anic verse interpretation, hadith study, and the perspectives of Companions and scholars. The findings reveal that ar-Radha’ah significantly influences the formation of mahram relationships, restricting marriage between specific individuals. This law is rooted in the Qur'an (Surah An-Nisa: 23) and authentic hadith and is reinforced by the Companions' ijtihad, such as Umar bin Khattab's contribution to setting a breastfeeding limit for establishing mahram ties. The Companions' interpretations have shaped a more detailed legal understanding, providing a flexible and contextual foundation. This study contributes to enhancing the modern relevance of ar-Radha'ah, aligning with Islamic law's focus on public interest.